Language transfer in translation: The case of lexico-semantic transfer and its impact on lexical correspondence/non-correspondence between languages - Zahri HAROUNI (Revue des Sciences Humaines, 1998)
Lexical relations, Collocations and false friends Constitute the most significant areas of negative language transfer in translation. These aspects of interlingual lexical contrast illustrate the considerable difficulties that foreign language students face when they translate forms and expressions from a source longuage into a target longuage. Translation, in such cases, instead of being a learning and problem-solving strategy often results in lack of lexical correspondence between the source language and the target language, inappropriateness to the context and sometimes even to something not possible in the target language, i.e., semantically non-permissible.